Neutrophils Culture in Collagen Gel System - Li, Ru; Wang, Ziqing; Huang, Junhao; He, Sixiao; Peng, Yanmei; Wan, Yong; Ma, Qiang (Frontiers in Immunology, 2022)
Neutrophils(Neu) play important roles in immune system related diseases, including sepsis，ischemia reperfusion, tumor, and so on, because the neutrophil culture system is indispensable for their function research, the existing culture system should be optimized to prolonging the life span of Neu and maintaining their activity. In this study, we developed a new 3D culture system for Neu, which is made of hydrogel. The Neu showed much better cell intergrity and less cell debris in the 3D culture system compared to that in 2D culture system. Moreover, the 3D culture system is more suitable for the observation of NETs (neutrophil extracellular traps) phenomenon produced by Neu through PMA (phorbol ester) stimulation than 2D culture system , and NETs phenomenon in 3D culture system is similar to that in vivo. In addition, the 3D culture system was evaluated to co-culture Neu and other parenchymal cells, such as skeletal muscle cells. In conclusion, the 3D culture system could maintain better properties of Neu than that in 2D culture system and it is possible to replace some in vivo experiments.